The Relationship Between Carrot Juice Consumption, the Level of Constipation in Pregnant Women at Alisah Clinic in 2025 - Irka Setiawati; Afrida Yelni; Chandra Julita Pasaribu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Constipation is a common problem experienced by pregnant women, mainly caused by physiological changes during pregnancy, such as increased levels of progesterone which slow down intestinal peristalsis, as well as the pressure exerted by the growing uterus on the digestive tract. This condition often leads to abdominal discomfort, pain, and may interfere with the quality of life of expectant mothers if left untreated. One natural approach that can be utilized to alleviate constipation is the consumption of carrot juice. Carrots are rich in dietary fiber, water, vitamins, and minerals, all of which play an important role in maintaining a healthy digestive system. Regular intake of carrot juice is expected to improve bowel movement frequency, soften stool consistency, and help reduce constipation symptoms in pregnant women. In addition, carrot juice provides essential nutrients that support fetal growth and development. Therefore, the use of carrot juice can be considered a safe, simple, and nutritious alternative to support digestive health during pregnancy.